EVALUATION OF INDONESIAN LANGUAGE LEARNING BASED ON CURRICULUM IMPLEMENTATION WITH INPUT, PROCESS, AND PRODUCT MODEL IN THE PILOT JUNIOR HIGH SCHOOLS - Mulyati, Sri; Nurkamto, Prof. Dr. Joko; Suwandi, Prof.Dr. Sarwiji; Slamet, Prof. Dr. St.Y.; Andayani, Prof. Dr. (IJRDO- Journal of Educational Research, 2017)
This study aims at finding the strengths and the weaknesses of the program implementation of 2013 curriculum, particularly the implementation of Indonesian language learning at The Pilot Junior High School for the implementation of 2013 curriculum.The research used descriptive qualitative research method by applying the model of Context, Input, Process, Product (CIPP) evaluation. The evaluation by using CIPP framework aimed at describing all the elements that contribute to the implementation of the program. Context is to describe the characteristics of students, teachers, and infrastructure; Input is to describe the preparation of lesson plans; Process is to describe the implementation of the learning process, and Product is to outline the results of student achievement.The results showed: (1) Context, the characteristics of students, teachers, and infrastructure, in general, are good, seen from the attitudes, interests, and student’s high competence, and the teacher’s ability and experience are great, and sufficient infrastructure of the learning support. (2)Input, the teacher is not optimal in preparing lesson planning materials, seen from the use of the learning plan of Discussion Of Subject Teachers. (3) The process, generally well performed, shown by the application of textbased learning approach, the use of scientific approaches, methods, and instructional media under the provisions of the Education Process Standards, although the use of learning resources and assessment of learning not implemented effectively. (4) The Product showed good results, seen from the average achievement of learning outcomes of each end of the semester and results of National Examination, which exceeded the minimum completeness criteria.